2008
DOI: 10.1111/j.1365-2036.2008.03644.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: novel therapeutic options for chronic hepatitis C

Abstract: SUMMARY BackgroundThe efficacy of treatment against hepatitis C virus has improved, but it is still far from ideal. Thus, new antihepatitis C virus therapies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 95 publications
1
33
0
1
Order By: Relevance
“…Although PEG-IFN and RBV have always been included in HCV treatments, their limited efficacy and frequent side effects have encouraged the search for a better alternative 8. Direct-acting antiviral agents, which have a different approach in targeting the life cycle of HCV, have been developed and approved by the US FDA 29,30…”
Section: Discussionmentioning
confidence: 99%
“…Although PEG-IFN and RBV have always been included in HCV treatments, their limited efficacy and frequent side effects have encouraged the search for a better alternative 8. Direct-acting antiviral agents, which have a different approach in targeting the life cycle of HCV, have been developed and approved by the US FDA 29,30…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotides research is considered a very promising technology for use in the development of drugs with both high target specificity and reduced side effects. Studies have demonstrated antisense inhibition of viral gene expression in biochemical assays, in cultured cells and in animal models [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Currently, there is ongoing antisense oligonucleotides research targeting human cytomegalovirus and human immunodeficiency virus, which is being evaluated in clinical trials.…”
Section: Delivery Of Antisense Therapymentioning
confidence: 99%
“…A targeted novel approach of delivering antisense therapy and other entities which are typically too problematic to deliver may be instrumental. Therefore achieving a combination of targeted delivery of oligonucleotides, other genetic disrupters and other viral targets not normally feasible with current systems may be advantageous [31,32,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102].…”
Section: Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although major achievements in hepatitis C treatment have been accomplished during the past decade, the future therapeutic approach will certainly rely on specifically targeted antiviral therapies (STAT-C) against essential viral proteins, especially for subjects who had no response to or had experienced relapses after receipt of current combination treatment with pegylated interferon and ribavirin [7]. Indeed, these new molecules have shown very good potency in in vitro assays, particularly against HCV-1 strains.…”
mentioning
confidence: 98%